Good Corporate Governance Practices as a Model for Organisational Performance - Gune, P.B; Bhebhe, T.B (IJRDO - Journal of Business Management, 2020)
The study sought to assess the existence of good corporate governance practices in the Non-Governmental Organisations (NGOs) sector in Zimbabwe and how the existence or absence of the good corporate governance practices affected their organisational performance. The study was carried out in five NGOs whose headquarters are in Harare Metropolitan Province. The research used descriptive research design and questionnaires to collect primary data for analysis before drawing conclusions. The findings show that some Non-Governmental Organisations (NGOs) have bad corporate governance practices: Audits are not done regularly, there are poor ethical practices and some of the NGOs’ activities were not transparent. The boards were not effective as no clear policies for the replacement of board members existed in the NGOs. The study recommended Non-Governmental Organisations to adopt corporate governance best practices in order to improve performance, accountability and to protect the interests of stakeholders.